Efficacy and rule of dilemmas in administrative criminal law (Academic Journal of Internal Affairs, 2015)
The author provides an overview of the theoretical difficulties in positioning administrative criminal law alongside criminal law and administrative law.
Keywords: criminal law; administrative law; dilemmas